Factors Affecting The use Of Posbindu PTM Elderly In Medan Puskesmas Rantang Medan District Medan Petisah District In 2018 - Sri Natalia Ginting; Asriwati Asriwati; Anto Anto (STIKes Hang Tuah Pekanbaru, 2020)
Non-communicable diseases have become the leading cause of death globally at this time. Posbindu PTM is a form of service that involves community participation through promotive-preventive efforts. This type of research is a mixed methods approach with the aim to find out the factors that influence the utilization of Posbindu PTM in the elderly in the Work Area of ​​Rantang Medan Puskesmas Medan Petisah District with a population of 653 elderly with a sample technique using accidental sampling as many as 87 elderly. The results showed that knowledge had a sig-p 0.011 <0.05, an attitude of sig-p 0.017> 0.05, a distance of sig-p 0.041 <0.05, support of health personnel sig-p 0.415> 0.05 and family support have a p-p 0.028 <0.05. The conclusion is the influence of knowledge, attitudes, distance and family support for the use of Posbindu PTM in the elderly, while the support of health workers does not have an influence on the use of Posbindu PTM in the elderly. This research is expected to be a useful input or information for Puskesmas, Health Services, and other agencies related to the use of Posbindu PTM. Key word : Influencing Factors, Utilization of Posbindu PTM, Elderly